Paciente de sexo femenino de 4 años de edad con anemia moderada y desnutrición crónica - Muñoz Sánchez, Deyanira Julissa (2021)
This case presents a 4-year-old female patient with moderate anemia and chronic malnutrition, in this clinical case the anthropometric, biochemical, clinical and dietary values will be evaluated, in order to achieve the diagnosis in which it is find the patient and in this way provide her with the appropriate nutritional treatment. The objective is to cover the nutritional needs according to each pathology of the patient and establish a nutritional plan with the macro and micronutrients that are in deficit and that are damaging the health of the patient. Iron deficiency anemia can be of deficiency or non-deficiency origin and depending on the degree of anemia; treatment will be with oral iron accompanied by a varied and balanced diet. In addition to this, there is also the relationship that anemia has with chronic malnutrition, which in turn is linked to the mother's gestation period and the first two years of life, where the child has not received the necessary nutrients and as a consequence will have a weaker immune system being prone to developing diseases. (Garcia, 2016). By means of the food anamnesis that was carried out on the mother of the patient, it reflects the feeding of the girl where it can be verified if there is an insufficient supply of nutrients or either by the continuous presence of infectious diseases or parasitosis causing her to present delay growth, having irreversible consequences both physically and psychologically.